Sleep Quality, Sleep Duration, and the Risk of Adverse Clinical Outcomes in Patients With Myocardial Infarction With Non-obstructive Coronary Arteries - Zhu, Chun-Yan; Hu, Hui-Lin; Tang, Guan-Min; Sun, Jing-Chao; Zheng, Hui-Xiu; Zhai, Chang-Lin; He, Chao-Jie (Frontiers in Cardiovascular Medicine, 2022)
Background Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a heterogeneous entity with varying underlying etiologies and occurs in 5–10% of patients with acute myocardial infarction. Sleep disorders and short sleep duration are common phenomena experienced by patients with coronary heart disease and are associated with poor clinical outcomes. However, the association between sleep quality, sleep duration, and the MINOCA prognosis is less clear. Methods We performed a prospective observational study of 607 patients with MINOCA between February 2016 and June 2018. The mean follow-up period was 3.9 years. Sleep quality and sleep duration were measured by the Chinese version of the Pittsburgh Sleep Quality Index. The primary endpoint was all-cause mortality, and the secondary endpoint was major adverse cardiovascular events (MACE), defined as a composite of cardiovascular death, non-fatal myocardial infarction, stroke and heart failure hospitalization. Results During the follow-up period, all-cause death occurred in 69 participants and 105 participants developed MACE. The Kaplan–Meier survival analysis demonstrated a significant association between poor sleep quality and all-cause mortality (log-rank P = 0.005) and MACE (log-rank P = 0.004). Multivariable Cox regression model indicated that poor sleep quality was an independent predictor of all-cause mortality as well as MACE [adjusted hazard ratio (HR) = 1.649; 95% confidence interval (CI), 1.124–2.790; P < 0.001; and adjusted HR = 1.432; 95% CI, 1.043–2.004; P = 0.003, respectively]. For sleep duration, short sleep duration (<6 h/d) was significantly associated with an increased risk of all-cause mortality and MACE (adjusted HR = 1.326; 95% CI, 1.103–1.812; P = 0.004; and adjusted HR = 1.443; 95% CI, 1.145–1.877; P < 0.001, respectively), whereas long sleep duration was not (>8 h/d). A poorer sleep profile (including poor sleep quality and short sleep duration) was associated with a 149.4% increased risk of death (HR = 2.494; 95% CI, 1.754–4.562; P < 0.001) and a 96.7% increased risk of MACE (HR = 1.967; 95% CI, 1.442–3.639; P < 0.001) than those with neither. Conclusion Sleep disorders were common among Chinese patients with MINOCA. Poor sleep quality and short sleep duration were independently associated with an increased risk of all-cause mortality and MACE in the MINOCA population. Meanwhile, a poor sleep profile has an additive effect with regard to cardiovascular risks; in these populations, efforts should be made to improve both sleep quality and sleep duration for secondary cardiovascular prevention. Clinical Trial Registration http://www.chictr.org.cn, identifier: ChiCTR2000040701.